Meritve sončnega sevanja v gozdu - Diaci, Jurij (Zbornik gozdarstva in lesarstva, 1999)
Solar energy sustains ecosystems on earth, therefore solar radiation measurements are the basis for ecological research in forests. Silviculturistsin particular should be aware at least of the basic principles of radiation distribution in forest vegetation. There has been a rapid development of methods and devices in the field of solar radiation measurement. In the paper, solar radiation is presented as one of the most important ecological resources and factors. The author demonstrates how significant this knowledge is in silviculture. The main topic is the presentation of recognized methods for solar radiation measurement and estimation in forests. Comparing these different methods we find Photosynthetically Usable Radiation (PUR) sensors to be very appropriate for complex research in forest vegetation. It is advantageous to use multiple PUR sensors connected to a computer for data processing. Another method for estimating radiation which has great potential is the one using hemispherical photography. The same principle is applied in a fixed horizontoscope which is particularly appropriate in silvicultural practice.
Keywords: gozdovi; merjenje; metode; sončno sevanje